Hydrolyzed whey protein enriched with glutamine dipeptide attenuates skeletal muscle damage and improves physical exhaustion test performance in triathletes - Peres, Fabiano Pinheiro; Levada-Pires, Adriana Cristina; Vieira, Marcelo; Hatanaka, Elaine; Cury-Boaventura, Maria Fernanda; Folador, Alessandra; Gorjão, Renata; Hirabara, Sandro Massao; Santos-Silva, Paulo Roberto; Deuster, Patricia A.; Curi, Rui; Pithon-Curi, Tania Cristina (Frontiers in Sports and Active Living, 2023)
Purpose To investigate the effects of hydrolyzed whey protein enriched with glutamine dipeptide on the percentage of oxygen consumption, second ventilatory threshold, duration and total distance covered, and skeletal muscle damage during an exhaustion test in elite triathletes. Methods The study was a randomized, double-blinded, placebo-controlled, crossover trial. Nine male triathletes performed a progressive incremental test on a treadmill ergometer (1.4 km h−1·3 min−1) 30 min after ingesting either 50 g of maltodextrin plus four tablets of 700 mg hydrolyzed whey protein enriched with 175 mg of glutamine dipeptide diluted in 250 ml of water (MGln) or four tablets of 700 mg maltodextrin plus 50 g maltodextrin diluted in 250 ml of water (M). Each athlete was submitted to the two dietary treatments and two corresponding exhaustive physical tests with an interval of one week between the interventions. The effects of the two treatments were then compared within the same athlete. Maximal oxygen consumption, percentage of maximal oxygen consumption, second ventilatory threshold, and duration and total distance covered were measured during the exhaustion test. Blood was collected before and immediately after the test for the determination of plasma lactate dehydrogenase (LDH) and creatine kinase (CK) activities and lactate concentration (also measured 6, 10, and 15 min after the test). Plasma cytokines (IL-6, IL-1β, TNF-α, IL-8, IL-10, and IL-1ra) and C-reactive protein levels were also measured. Results A single dose of MGln increased the percentage of maximal oxygen consumption, second ventilatory threshold duration, and total distance covered during the exhaustion test and augmented plasma lactate levels 6 and 15 min after the test. MGln also decreased plasma LDH and CK activities indicating muscle damage protection. Plasma cytokine and C-reactive protein levels did not change across the study periods. Conclusion Conditions including overnight fasting and a single dose of MGln supplementation resulted in exercising at a higher percentage of maximal oxygen consumption, a higher second ventilatory threshold, blood lactate levels, and reductions in plasma markers of muscle damage during an exhaustion test in elite triathletes. These findings support oral glutamine supplementation's efficacy in triathletes, but further studies require.